MEDIA PEMBELAJARAN MONOPOLI UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR PESERTA DIDIK PADA MATERI KALOR - Detty, Elisabeth; Tandililing, Edy; Mahmudah, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this study was to increase the interest and learning outcomes of students in heat material using monopoly game learning media. This research was conducted in class VII E SMP Negeri 13 Pontianak, this was done based on the results of research that showed the average learning outcomes of students in the heat material is quite low, which is 42. One of the causes is the student’s low interest in learning physics material. Therefore this study used monopoly game learning media so that it would create fun atmosphere in learning, thus the student’s learning interest will begin to grow in harmony with the learning outcomes of students. The participants' interest in learning was carried out using questionnaires, while the learning outcomes of students were conducted using questions test such as multiple choice. The results showed that the student’s  learning interest increased by 10.19%, while the student’s learning outcomes also experienced an increase in this, indicated by the results of the t test, where tcount> t table (10.48> 1.708). Monopoly game learning media could increase student’s interest and learning outcomes, it is expected to be one of the alternative teaching media that help increase students' interest and learning outcomes.  Keywords: Interests, Learning Media, Monopoly, and Learning Outcomes